Bayesian calibration at the urban scale: a case study on a large residential heating demand application in Amsterdam. Issue 3 (3rd May 2020) - Wang, Cheng-Kai; Tindemans, Simon; Miller, Clayton; Agugiaro, Giorgio; Stoter, Jantien
ABSTRACT: A bottom-up building energy modelling at the urban scale based on Geographic Information System and semantic 3D city models can provide quantitative insights to tackle critical urban energy challenges. Nevertheless, incomplete information is a common obstacle to produce reliable modelling results. The residential building heating demand simulation performance gap caused by input uncertainties is discussed in this study. We present a data-driven urban scale energy modelling framework from open-source data harmonization, sensitivity analysis, heating demand simulation at the postcode level to Bayesian calibration with six years of training data and two years of validation data. Comparing the baseline and the calibrated simulation results, the averaged absolute percentage errors of energy use intensity in the study area have significantly improved from 25.0% to 8.3% and from 19.9% to 7.7% in two validation years, while C V R M S E 2016 = 11.5 % and C V R M S E 2017 = 13.2 % . The overall methodology is extendable to other urban contexts.